PATHOMORPHOLOGICAL CHARACTERISTICS OF OVARIAN TUMORS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Ovarian tumors represent a heterogeneous group of neoplasms with diverse pathomorphological characteristics that significantly impact diagnosis, prognosis, and treatment decisions. Understanding the detailed morphological features is crucial for accurate classification and optimal patient management. To analyze the pathomorphological characteristics of ovarian tumors, examine their distribution patterns, and correlate morphological features with clinical outcomes. A retrospective analysis of 847 ovarian tumor cases was conducted over a 5-year period, examining histopathological features, immunohistochemical profiles, and clinical correlations. Epithelial tumors comprised 75.2% of cases, followed by sex cord-stromal tumors (12.8%) and germ cell tumors (8.1%). Serous carcinomas showed the highest grade of nuclear atypia and mitotic activity, while mucinous tumors demonstrated characteristic intestinal-type epithelium in 68% of cases.